China's Industrialization Process - Huang, Qunhui (Research Series on the Chinese Dream and China's Development Path,, 2018)
Based on long-term research, this book comprehensively and systematically discusses the industrialization process in China, analyzing the level, characteristics, achievements and experiences as well as the problems faced. It also provides answers to important questions related to economic development and the industrialization process in China, such as what level of industrialization China has achieved and whether China can become an industrialized country. Lastly, it offers an explanation of China's economic development from the perspective of industrialization.